2018
DOI: 10.1186/s12871-018-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for the prediction of postoperative hypoxemia in patients with acute aortic dissection

Abstract: BackgroundPostoperative hypoxemia is quite common in patients with acute aortic dissection (AAD) and is associated with poor clinical outcomes. However, there is no method to predict this potentially life-threatening complication. The study aimed to develop a regression model in patients with AAD to predict postoperative hypoxemia, and to validate it in an independent dataset.MethodsAll patients diagnosed with AAD from December 2012 to December 2017 were retrospectively screened for potential eligibility. Preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 32 publications
10
41
1
Order By: Relevance
“…According to reports, the incidence of hypoxemia after AD is 20.4-49.5% [23]. Kazmierski et al [23] indicated that postoperative hypoxemia (PaO2 < 60 mmHg) was an independent risk factor for delirium after cardiac surgery. In this research, we found that the incidence of hypoxemia during and after AD surgery was 24.29%.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, the incidence of hypoxemia after AD is 20.4-49.5% [23]. Kazmierski et al [23] indicated that postoperative hypoxemia (PaO2 < 60 mmHg) was an independent risk factor for delirium after cardiac surgery. In this research, we found that the incidence of hypoxemia during and after AD surgery was 24.29%.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, the incidence of hypoxemia after AD is 20.4%-49.5% [23] . Kazmierski et al [23] indicated that postoperative hypoxemia (PaO2 < 60mmHg) was an independent risk factor for delirium after cardiac surgery. In this research, we found that the incidence of hypoxemia during and after AD surgery was 24.29%.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram as a visualization tool has been widely used in clinical prognosis research on critical patient and cancer patient survival studies (12)(13)(14). The primary aim of the present study is to develop a novel prediction nomogram for the 28-day mortality risk in SIC patients.…”
Section: Introductionmentioning
confidence: 99%